A prediction model for detrusor overactivity at ambulatory urodynamics in women with urinary incontinence. (August 2020) - Seval, Mehmet Murat; Çetinkaya, Şerife Esra; Kalafat, Erkan; Dökmeci, Fulya
Highlights: A multivariable model was investigated to predict the presence of detrusor overactivity in women with urinary incontinence. Higher body mass index, overactive bladder awareness tool version 8 scores and the presence of urgency urinary incontinence were positively associated with detrusor overactivity. Postural urinary incontinence and insensible loss of urine were negatively associated with detrusor overactivity. Abstract: Objective(s): To develop a multivariable model using both clinical examination findings and validated questionnaires' scores for predicting the presence of detrusor overactivity observed during ambulatory urodynamic monitoring in women with urinary incontinence. Study Design: The study population was chosen from a registry of women evaluated with urodynamics for urinary incontinence retrospectively. Data for baseline characteristics, clinical findings, and ambulatory urodynamic records were evaluated for all women included to the study. Urodynamic data were obtained by retrospective review of urodynamic traces with a standardized protocol during single voiding cycle, compatible to the standards of International Continence Society (ICS) for ambulatory urodynamic monitoring. Results: A total of 395 women with urinary incontinence were included in the study. Detrusor overactivity was diagnosed in 57.1% of women included to the study. Clinical factors positively associated with detrusor overactivity were higher body-mass index (OR = 1.10; 95% CI 1.03−1.15, p  < 0.001), higher OAB-V8 (Overactive bladder awareness tool - version 8) scores (OR = 1.04; 95% CI 1.01−1.06, p  < 0.001) and presence of urgency urinary incontinence (OR = 2.39; 95% CI 1.47−3.81, p  < 0.001). The presence of postural urinary incontinence (OR = 0.51; 95%CI 0.28−0.90, p = 0.021) and insensible loss of urine (OR = 0.33; 95%CI 0.27−0.93, p = 0.005) had negative associations with detrusor overactivity in the final multivariate logistic regression analysis. Conclusion(s): BMI, OAB-V8 scores, urgency urinary incontinence, postural urinary incontinence and insensible loss of urine were associated with the presence of detrusor overactivity according to our prediction model. However, the overall model accuracy suggests urodynamic studies are still needed for a definitive diagnosis. Nevertheless, the prediction may be beneficial for selecting a subgroup of women who are unlikely to benefit from ambulatory urodynamic monitoring for the diagnosis of detrusor overactivity.